PROBEMATICS AND CHALLENGES OF THE EDUCATION SYSTEM IN INDONESIA - Muhammad Arif Nugraha; Adang Hambali (STIT PRINGSEWU, 2023)
There are quite a lot of educational problems in Indonesia today, starting from curriculum issues, quality, competencies, even leadership competencies, both at the top and bottom levels. Various cases of complaints occurred in the field, both school leaders and educators who regretted the dimensions of leadership such as matters of management, discipline, bureaucracy and administration that were in disarray. Then, no less important, leadership in schools also plays a role in coloring the face of the world of education and widens the gaps and internal conflicts of educators. The research method used in this research is the literature study method. The literature study method is a method used by the author by searching, collecting, exploring, or examining various references or documents related to the topic proposed, for this study one related article was used to support research supported by various other research sources. In Indonesia, readiness to face the challenges of education today is to immediately improve the capabilities and skills of Indonesian human resources through education and reliable analysts in the field of education management as a driving force for the progress of information technology-based education in Indonesia to answer these challenges. Some of the solutions that can be done include, among others, the suitability of the curriculum and policies in education, the readiness of human resources in utilizing ICT, optimizing the abilities of students, and developing the values ​​(character) of students. But until now the challenges of education are at least in 3 big aspects. First, the geographical aspect where the various geographical conditions, and the distance that separates the islands in Indonesia. Second, social diversity where despite the drastic decline in illiteracy and dropout rates over the last 50 years, there are still disparities in the quality of education between urban, rural and remote areas. Third, a teaching culture that is more oriented towards the assumption of knowledge targets that students should master.